Simulation of adverse factors of mining production influence on stomatological health of mining workers - Glazunov, O. A. (Journal of Education, Health and Sport, 2017)
Mathematical modeling of the unfavorable mining factors influence with the help of basic dental indices such as CPITN, PMA, KPU has been carried out. The relationship of these indices with the adverse effect of mining on the dental health of miners was has been established. It has been revealed that with accumulation of job seniority, paraclinical indices negatively change significantly.